Effect of Work Professionalism and Work Climate On Work Effectiveness at PT. Big Tour & Travel Post Pandemic Covid-19 in Indonesia - Indah Kusumawati Indah; Muhammad Abdul Rosid (Formosa Journal of Science and Technology, 2022)
This study aims to analyze the effect of Work Professionalism and Work Climate on Work Effectiveness at PT. BIG Tours & Travels. The population in this study were 57 employees where all employees were used as research samples. The method used is the quantitative method. Primary data collection was obtained from distributing questionnaires and secondary data obtained directly from the Company through the process of observation and interviews. The analytical technique used is multiple linear regression analysis using SPSS version 24 software. The results showed that the regression coefficient of Work Professionalism (X1) was 0.567, which was positive. This is indicated by the t-count value of 3.992 which is greater than the t-table of 2.005, and a significance value of 0.000 below 0.05. Where Professionalism Work (X1) partially positive and significant effect on Work Effectiveness (Y). While the regression value of Work Climate (X2) is 0.245, positive value, this is indicated by the t-count value of Work Climate of 1.846 which is smaller than t table of 2.005, and a significance value of 0.070 is greater than 0.05. Where the work climate (X2) has a positive and insignificant effect on work effectiveness (Y). So it can be said that Work Professionalism (X1), and Work Climate (X2) simultaneously have a positive effect on Work Effectiveness (Y) With the value of the multiple regression equation Y = 6.371 + 0.567X1 + 0.245X2 with a coefficient of determination of 41.10%, the rest is influenced by other factors not studied.